A transistorized Rocketsonde for measurement of upper atmosphere temperature (MAUSAM, 1968)
This note gives description of & pulse modulated transistorized rocketsonde instrument package, working on 1680 Mc/s for telemetering temperature information from meteorological sounding rockets. Currently used ground equipments like GMD-1 or WBRT-57 can be used to receive the signals. The package is completely transistorized except for the final transmitting stage which has a sub-miniature tube. H.T. battery, however, is not required for this tube. The change in resistance of the thermistor due to variation in tempernture changes the p.r.f. of the  modulator between 10 to 200 cps.